Women’s Knowledge and Biodiversity of Lou Dempar Cultural Community in A "Fire Cloud Smoke/Api Awan Asap" Novel Written by Korrie Layun Rampan: Ecofeminism Study - Furoidatul Husniah; Haris Supratno; Tengsoe Tjahjono (Pancaran Pendidikan, 2019)
This research aimed to describe the relationship between women and nature in maintaining and preserving the natural environment. The relationship was illustrated in problems 1) the existence of patriarchal power on women of Lou Dempar, which causing sexual violence in the "Fire Cloud Smoke/Api Awan Asap" novel; 2) women's intelligence due to the knowledge they had in maintaining the biodiversity of Lou Dempar in the "Fire Cloud Smoke/Api Awan Asap" novel; 3) women's intelligence in preserving the traditions of the ancestors of Lou Dempar in the "Fire Cloud Smoke/Api Awan Asap" novel. This research used descriptive qualitative research with an ecofeminism approach. There were 2 kinds of data in this research, they were primary data consisting of words, phrases and sentences quoted from the "Fire Cloud Smoke/Api Awan Asap" novel written by Korrie Layun Rampan, while the secondary data were in the form of other data obtained from the reading of journals, books, newspapers that had a relation with primary data. The research data were collected by using the documentation technique. Data analysis techniques used were identification, classification, analysis, and triangulation. The results and discussion stated that patriarchal power penetrated nature and women became the victims, but Nori appeared as a representation of a woman who had the knowledge and also thought in advancing the village by taking care of nature or biodiversity. The Lou Dempar community rose up in terms of agriculture, animal husbandry, mastery of modern technology, and marketing of agricultural products. Women's knowledge was able to preserve nature, including preserving the hereditary traditions of Lou Dempar cultural community. Vandana sHiva's ecofeminism showed the relationship between women's knowledge, protecting culture and biodiversity.